Nutrition Class by Instagram: Interventions to Improve The Diet Quality, Physical Activity and Waist Circumfeence Among Female College Students with Obese - Fillah Fithra Dieny; Deny Yudi Fitranti; Firdananda Fikri Jauharany; Suryawati Suryawati; A. Fahmy Arif Tsani; Ayu Rahadiyanti (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Female students are a group of women of childbearing age (WUS) or preconception. Obesity in WUS or the preconception period can interfere with future pregnancies and interfere with metabolism and hormones. Obese women with obesity need to change their behavior so that it needs increased knowledge and motivation as a basis for behavior change. This research objective was to determine the effect of nutrition education and motivation classes on the practice of healthy weight loss in obese women. This quasi-experimental research with pre-posttest control group design on 24 female women who met the inclusion criteria was divided into 2 groups using the simple randomization method. The independent variable is the Instagram Nutrition School program for 1 month, consisting of nutritional counseling with a motivational interviewing strategy and social media-based nutrition education classes on Instagram, while the control group is given education through leaflet media. The dependent variable is knowledge of healthy weight loss, quality of diet and changes in anthropometric profiles, namely body weight, body mass index, waist circumference and percent body fat. Independent T-test and Mann Whitney test were used to assess differences in knowledge scores on healthy weight loss, diet quality, and differences in anthropometric deltas. There was a significant difference in knowledge score (p= 0.002), score of moderation (p= 0.001), total physical activity score (p= 0.002), and moderate physical activity (p less than 0.001), mean waist circumference (p = 0.047), and waist circumference (p= 0.032) after intervention. The Instagram Nutrition School Program has been proven to increase nutritional knowledge, change eating behavior, and increase physical activity. Abstrak: Mahasiswi merupakan kelompok Wanita Usia Subur (WUS) atau prakonsepsi. Obesitas pada WUS atau periode prakonsepsi dapat mengganggu kehamilan di masa depan dan mengganggu metabolisme dan hormonal. WUS obesitas perlu merubah perilaku sehingga dibutuhkan peningkatan pengetahuan dan motivasi sebagai dasar perubahan perilaku. Penelitian ini bertujuan untuk mengetahui pengaruh edukasi gizi dan kelas motivasi terhadap praktik healthy weight loss pada WUS obesitas. Penelitian quasi-experimental with pre-post test control group design pada 24 WUS yang memenuhi kriteria inklusi dibagi menjadi 2 kelompok dengan metode simple randomization. Variabel bebas adalah program Sekolah Gizi Instagram  selama 1 bulan, terdiri dari konseling gizi dengan strategi motivational interviewing dan kelas edukasi gizi berbasis sosial media Instagram, sedangkan kelompok kontrol diberikan edukasi melalui media leaflet. Variabel terikat adalah pengetahuan healthy weight loss, kualitas diet dan perubahan profil antropometri yaitu berat badan, indeks massa tubuh, lingkar pinggang dan persen lemak tubuh. Independent T-test dan Mann Whitney Test digunkaan untuk mengkaji perbedaan skor pengetahuan healthy weight loss, kualitas diet, dan perbedaan delta antropometri. Terdapat perbedaan yang signifikan pada skor pengetahuan (p=0,002), skor moderasi (p=0,001), skor total aktifitas fisik (p=0,002), dan aktifitas fisik sedang (p kurang dari 0,001), rerata lingkar pinggang (p=0,047), dan lingkar pinggang (p=0,032) setelah intervensi. Program Sekolah Gizi Instagram terbukti meningkatkan pengetahuan gizi, merubah perilaku makan, dan meningkatkan aktivitas fisik.